Pricing of bonds and equity when the zero lower bound is relevant - Heinrich Kick (European Central Bank (ECB), 2017)
This paper investigates the joint dynamics of nominal bond yields, real bond yields and dividend yields from the 80s up to the aftermath of the financial crisis by mapping them on a set of macro factors. It builds on an existing discrete time affine Gaussian model of the term structure model of nominal bonds, real bonds and equity and extends it by three important innovations. Firstly, allowing for structural shifts in inflation expectations. Secondly, accounting for the relevance of the zero lower bound in the period after 2008 by modelling a so-called shadow rate and deriving asset prices by explicitly considering the zero lower bound. Finally, calculating the standard errors to correctly capture the multi-step nature of the estimation process, which results in substantially larger standard errors than previously reported for the model. We achieve statistically signicant risk premia by imposing restrictions on the matrix of risk premia. Taken together, these modifications allow to better model asset prices also during the financial crisis and the ensuing economic environment of sluggish growth, low inflation rates, interest rates close to zero and quantitative easing.
Keywords: C13; E43; G12; 330; asset pricing; financial crisis; zero lower bound